2015
DOI: 10.1037/abn0000078
|View full text |Cite
|
Sign up to set email alerts
|

Functional coherence of insula networks is associated with externalizing behavior.

Abstract: The externalizing spectrum encompasses a range of maladaptive behaviors, including substance use problems, impulsivity, and aggression. While previous literature has linked externalizing behaviors with prefrontal and amygdala abnormalities, recent studies suggest insula functionality is implicated. The present study investigated the relation between insula functional coherence and externalizing in a large community sample (N=244). Participants underwent a resting functional magnetic resonance imaging scan. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 97 publications
(168 reference statements)
0
36
0
Order By: Relevance
“…This means that persons with a high level of an externalizing personality share a higher risk of developing externalizing disorders than persons with a low level of an externalizing personality. Different brief versions of the full ESI of 415 items have been developed and research has shown moderate to high associations (r¼.22 to r¼.57) between these versions and antisocial behaviors in adulthood and childhood (Hall et al, 2007;Venables & Patrick, 2012), heightened levels of alcohol dependence and drug abuse (Venables & Patrick, 2012) and neural networks associated with disinhibition and antisocial behavior (Abram et al, 2015;Hall et al, 2007;Nelson et al, 2011). Extending this work, a 160-item version was developed by Patrick and colleagues (Patrick et al, 2013).…”
mentioning
confidence: 99%
“…This means that persons with a high level of an externalizing personality share a higher risk of developing externalizing disorders than persons with a low level of an externalizing personality. Different brief versions of the full ESI of 415 items have been developed and research has shown moderate to high associations (r¼.22 to r¼.57) between these versions and antisocial behaviors in adulthood and childhood (Hall et al, 2007;Venables & Patrick, 2012), heightened levels of alcohol dependence and drug abuse (Venables & Patrick, 2012) and neural networks associated with disinhibition and antisocial behavior (Abram et al, 2015;Hall et al, 2007;Nelson et al, 2011). Extending this work, a 160-item version was developed by Patrick and colleagues (Patrick et al, 2013).…”
mentioning
confidence: 99%
“…In addition, a relationship between substance abuse and the insula was supported by a recent fMRI study that identified a positive association between activity in the posterior insula, substance abuse and general disinhibition (Abram et al . ). In rodents, inhibition of protein synthesis in the insula disrupts drug‐related contextual memories (Contreras et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bertocci et al (2014) found that patterns of task-based prefrontal-amygdala functional connectivity were associated with distinct developmental trajectories of manic symptoms as derived through latent class growth analysis. Krueger and DeYoung (2016) described the hierarchical-dimensional model of psychopathology and its potential relevance to the study of RDoC constructs, citing a recent study with adult participants in which resting state imaging was used to examine the neural correlates of an externalizing symptom dimension and its purported subdimensions (antagonism, disinhibition, and substance abuse) (Abram et al, 2015). Coherence measures within different neural networks were differentially related to antagonism, disinhibition, and substance abuse symptoms.…”
Section: Discussionmentioning
confidence: 99%